Examining the Suitable Palliatives in Cushioning the Removal of Fuel Subsidy in Nigeria - Farouk Salami Adinoyi; Gbenemene Kpae (PT FORMOSA CENDEKIA GLOBAL, 2023)
Various operational indicators pinpoint fuel subsidy as a major instrument in poverty reduction in Nigeria. However, its removal in 2023 by the administration of president Bola Ahmed Tinubu may have constitute a major obstacle to Nigeria’s Poverty reduction. It has been contended and reiterated that several interventions in the form of palliatives may have significant improvement in cushioning the economic hardship of fuel subsidy removal. Plagued with the challenges of Conflicts, insecurity and insurgency, the debate on the suitable operational palliatives to cushion or reduce the economic hardship of fuel subsidy removal exacerbate this study. The operational theory for this study includes Progressive Social Theory, Geographical Disparities Theory, Cyclical Interdependence Theory and theory of Social Exclusion /Cumulative Disadvantage. The nature of the study was a qualitative one, and the content analysis method was used to analyse the secondary data. The study found that lack of transparency in previous palliatives particularly during Covid-19 pandemic fueled public skepticism in the present government fuel subsidy removal palliatives. It, therefore, recommends that there should be accountability and transparency in the distribution of fuel subsidy removal palliatives as a way of enhancing public confidence in the process.